Agricultural Markets’Analysis and Forecasting on the Base of Fractal Price Cycles Modelling - Iurkova, Marina; Lihovtsova, Еlena; Evsukova, Ludmila; Sadovnikova, Еlena (International Journal of Engineering and Technology, 2018)
The article is devoted to the agricultural markets’ analysis (grains and sunflower) as an integral system having its peculiarities which make it different from other markets. These specific features are connected with heterogeneity of participants following various aims and working in different investment horizons, as well as seasonal functioning of this market. The calculations have been given proving the E. Peters’ hypothesis on the presence of fractal agricultural markets. The research adjusts the use of the fractal markets’ analysis results in creating agrarian markets models and the possibility of forecasting its participants’ and prices behavior taking into consideration models’ data simplification.